BMSC-EV-derived lncRNA NORAD Facilitates Migration, Invasion, and Angiogenesis in Osteosarcoma Cells by Regulating CREBBP via Delivery of miR-877-3p. (1st March 2022) - Feng, Dapeng; Li, Zhengwei; Yang, Liang; Liang, Haidong; He, Hongtao; Liu, Lin; Zhang, Wei
Abstract : Bone marrow mesenchymal stem cells (BMSCs) can boost osteosarcoma (OS) cell proliferation and invasion, yet the function of extracellular vesicles (EVs) derived from BMSCs on OS is scarcely known. This study is aimed at examining the role of BMSC-EVs in OS cells. BMSCs and BMSC-EVs were isolated and identified. The effect of EVs and EVs-si-NORAD on OS cell proliferation, invasion, migration, and angiogenesis was determined. Expressions of NORAD, miR-877-3p, and CREBBP were detected. The binding relationship among NORAD, miR-877-3p, and CREBBP was verified. The miR-877-3p inhibitor or pc-CREBBP was delivered into OS cells treated with EVs-si-NORAD for in vitro analysis. The nude mouse model of the subcutaneous tumor xenograft was established for in vivo analysis. BMSC-EVs promoted OS cell proliferation, invasion, migration, and angiogenesis. BMSC-EVs carried NORAD into OS cells and upregulated CREBBP by sponging miR-877-3p. miR-877-3p downregulation or CREBBP overexpression partly inverted the inhibitory effect of EVs by silencing NORAD on OS cell proliferation, invasion, migration, and angiogenesis. In vivo experiments validated that BMSC-EV-derived NORAD facilitated tumor growth by upregulating CREBBP via miR-877-3p. To conclude, BMSC-EV-derived NORAD facilitated OS cell proliferation, invasion, migration, and angiogenesis by modulating CREBBP via miR-877-3p, which may offer new insights into OS treatment.